Pencegahan Kebiasaan Merokok di Dalam Rumah Melalui Upaya “GERAK MASBRO” - Dian Utami; Qonita Adzkia; Ucha Maulana; Evi Susanti Sinaga (CV. Multi Kreasi Media, 2024)
Smoking behavior in Indonesia is a major concern because of its impact on public health, especially with the increase in the number of adult smokers from 60,3 million in 2011 to 70,2 million in 2021 and the prevalence of smoking in adolescents aged 10-18 years from 7,2% to 9,1% in 2018. Men dominate adult smokers with a prevalence of 64,7%, while women are 2,3%. Smoking at home has a significant impact on the health of family members, especially women and children who are more vulnerable to exposure to passive cigarette smoke. Data shows that 56,8% of households are exposed to cigarette smoke, which increases the risk of heart disease, COPD, asthma, cancer, pneumonia, bronchitis, and SIDS. Therefore, education about the dangers of smoking at home is needed. This community service activity aims to increase public knowledge about the dangerous impacts of cigarette smoke and efforts to stop smoking at home through